The role of gut microbiota in intestinal and liver diseases - Hrncir, Tomas; Hrncirova, Lucia; Kverka, Miloslav; Tlaskalova-Hogenova, Helena (Laboratory animals, 2019)
The world-wide incidence of many immune-mediated and metabolic diseases, including those of the intestines and liver, is steadily increasing. Gut microbiota plays a central role in the pathogenesis of these diseases as it mediates environmental changes to the intestinal immune system. Various environmental factors including diet, food additives and medication also trigger the compositional and functional alterations of microbiota, that is, dysbiosis, and this dysbiosis is closely associated with many chronic inflammatory diseases. However, the causal relationship remains unclear for the majority of these diseases. In this review, we discuss essential epidemiological data, known pathogenetic factors including those of genetic and environmental nature, while mainly focusing on the role of gut microbiota in the development of selected intestinal and liver diseases. Using specific examples, we also briefly describe some of the most widely-used animal models including gnotobiotic models and their contribution to the research of pathogenetic mechanisms of the host-microbiota relationship.
Keywords: gnotobiologické modely; modely nemocí na zvířatech; Dysbiosis; cancer; Germ-Free Life; non-alcoholic fatty liver disease; coeliac disease; Gastrointestinal Microbiome; Intestinal Diseases; střevní mikroflóra; dysbiosis; Animals; zvířata; Disease Models, Animal; myši; dysbióza; nemoci střev; Liver Diseases; Mice; nemoci jater; inflammatory bowel disease